Simplified aptamer-based colorimetric method using unmodified gold nanoparticles for the detection of carcinoma embryonic antigen. Issue 15 (25th February 2015) - Luo, Cheng; Wen, Wei; Lin, Fenge; Zhang, Xiuhua; Gu, Haoshuang; Wang, Shengfu
<x xml:space="preserve">Abstract</x> A new colorimetric aptasensor for the detection of CEA was developed. Aptamer-based colorimetric method with nanoparticles was used for the detection of CEA. The colorimetric aptasensor has potential for the detection of other proteins or nucleotides.